To F-SIMS/XPS chemical depth profiling of synthetic polymer hydrogels - Taylor, Michael (2017)
Over the last decade the beneficial properties of hydrogels as artificial cell culture supports have been extensively investigated. Certain synthetic hydrogels have been proposed to be similar in composition and structure to the native extracellular matrix of the stem cell niche, their in vivo cell habitat, which is a powerful component in controlling stem cell fate. The stem cell differentiation pathway taken is influenced by many factors. When culturing cells within or upon hydrogels the choice can be strongly dependent on the underlying 3D hydrogel chemistry which strongly influences hydrogel-cell interactions.